Reconfigurações da noticiabilidade na pós-convergência: manifestações residuais no jornal Correio do Estado (MS) - Nathalia Lopes da Silva (2025)
This research aims to explore potential changes in the journalistic logic of newsworthiness (Shoemaker, 2006; Shoemaker, Cohen, 2006; Silva, 2013) within a peculiar regional geographic context—the newsroom of Correio do Estado, a media outlet located in Campo Grande, the capital of Mato Grosso do Sul. The study focuses on transformations in contemporary forms of sociability and in the modes of production, circulation, and consumption of symbolic goods within a culture of “post-media convergence” (Fagerjord, 2011; Nash, 2012; Ramírez, 2013). To achieve this, the research seeks to understand and debate the hypothetical dissolution of the traditional notion of temporal regularity as a central characteristic of production routines (Martín-Barbero, 2003; Thompson, 1998) and of the very conception of everyday life (Heller, 2016; Souza Martins, 2003) as a hegemonic cultural pattern of contemporary society (Berger and Luckmann, 1985; Giddens, 1991; Lipovetsky, 2005). The study reflects on how the contemporary deconstruction of the traditional notion of everyday life (Heller, 2016; Souza Martins, 2003) challenges the concepts of “media convergence” (Jenkins, 2001; 2008) and “journalistic convergence” (Salaverría; Negredo, 2008; Barbosa, 2009). These cultural constructions pave the way for the logic of “post-convergence” (Fagerjord, 2010; Nash, 2012; Ramírez, 2020), altering the very conception of news selection in a regional context. In other words, the research aims to propose a concept of journalistic post-convergence and its residual adherence in the practice of journalism in Mato Grosso do Sul. In terms of methodology, the study develops a bibliographic, theoretical-conceptual discussion to support the empirical phase of the research, which is based on the methodological model proposed by Lopes (2003). This model encompasses four research stages: a) epistemological (epistemic vigilance); b) theoretical (definition of reference frameworks); c) methodical (proposition of analytical frameworks); and d) technical (construction of empirical data and data analysis) (Lopes, 2003). After completing the procedures related to the first three stages, the technical stage involved three steps: 1) Direct observation in the Correio do Estado newsroom and semi-structured interviews with journalists from the outlet, considering differences such as gender, age, and hierarchical level. 2) Data processing through description. 3) Data interpretation based on theoretical-conceptual discussion and the systematization of results. The main findings include: a) confirmation of the idea that newsworthiness does not pertain to the intrinsic characteristics of an event but rather to the “personal judgment” (Shoemaker, 2016) inscribed in the collective sense-making of everyday life, determining whether an event has the potential to become news within the symbolic newsroom space, based on the dimensions of "deviation and social significance" (Shoemaker, 2014); b) events related to the local and regional context are less influenced by algorithms and digital metrics in the newsworthiness process; c) the dimensions of newsworthiness, such as deviation and social significance, involve aspects that encompass the socioeconomic and cultural context of Mato Grosso do Sul and its power dynamics; d) the process of newsworthiness in the context of Mato Grosso do Sul is also significantly shaped by its cultural, economic, and social specificities; e) the identification, albeit residual, of ongoing transformations in the newsworthiness process within a peculiar context of journalistic postconvergence.